Large interventricular membranous septal aneurysm renders the anatomy unsuitable for transcatheter aortic valve replacement. Issue 7 (11th April 2022) - Shirai, Yoshinori; Tanaka, Akihito; Tokuda, Yoshiyuki; Tobe, Akihiro; Furusawa, Kenji; Usui, Akihiko; Murohara, Toyoaki
Abstract: An interventricular membranous septal aneurysm, though rare, can coexist with aortic valve stenosis. In this report, we present an unsuitable anatomy for transcatheter aortic valve replacement (TAVR) due to large interventricular membranous septal aneurysm. This case suggests that the feasibility of TAVR would depend on the location and size of the aneurysm and its relationship with the aortic root.